2011
DOI: 10.1002/kin.20589
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical scavenging activities of silybin and its analogues: A pulse radiolysis study

Abstract: The flavonolignans (silybin and analogues) are important natural compounds with multiple biological activities operating at various cell levels. Many of these effects are connected with their radical scavenging activities. In the present study, free‐radical scavenging and antioxidant activities of four natural flavonoids, namely silybin, naringenin, naringin, and hesperetin, have been studied using nanosecond pulse radiolysis techniques. The kinetics and mechanisms of the reactions of silybin and analogues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Fu and others () used pulse radiolysis to evaluate the • OH‐scavenging activity of 3 flavanones: naringin (5), hesperetin (6), and naringenin (7). The rate constants and thus the • OH‐scavenging activity trended downward in the same order.…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fu and others () used pulse radiolysis to evaluate the • OH‐scavenging activity of 3 flavanones: naringin (5), hesperetin (6), and naringenin (7). The rate constants and thus the • OH‐scavenging activity trended downward in the same order.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Compound 5 showed the greatest activity, probably due to the presence of a sugar moiety with several hydroxyl groups. Fu and others () also performed a theoretical elucidation of the SAR. They calculated the O‐H bond dissociation energies (BDE) of the hydroxyl groups in the flavanones.…”
Section: Flavonoidsmentioning
confidence: 99%
“…This shows that naringin can effectively inhibit the occurrence of non-enzymatic browning in sprouts. Related studies have shown that naringin has excellent antioxidant and free radical scavenging ability, which can effectively reduce the production of free radicals in the organism [ 35 , 36 ]. The use of naringin forms an antioxidant film on the surface of the sprouts, which reacts preferentially with oxygen.…”
Section: Discussionmentioning
confidence: 99%